SISTEM PENDUKUNG PENGAMBILAN KEPUTUSAN REKRUTMEN GURU MENGGUNAKAN LOGIKA FUZZY TAHANI - Setiawan, Yayan Eryk (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2020)
One effort to get teachers who are competent in their fields is to conduct a teacher recruitment process based on four teacher competencies, namely personal, social, pedagogic, and professional competencies. However, the obstacle of the teacher recruitment process that often done is the subjectivity of decision-making. One way to overcome subjectivity in teacher recruitment is by using tahani fuzzy logic. For this reason, this study aims to determine the implementation of tahani fuzzy logic in the supporting system of decision making for teacher admissions based on the results of the four teacher competency tests. This research consists of three stages. The first stage is determining the function of the degree of membership from the value of personal, social, pedagogical, and professional competencies. The second step is designing the tahani fuzzification program using Microsoft Excel. The third stage is implementing the fuzzy tahani program that successfully created for the decision to make admissions. The results showed that teacher acceptance decision making using tahani fuzzy logic was better than just using an average value. Because tahani fuzzy logic considers various criteria, while the average only considers one criterion that has a high value.